Factors Affecting Distribution of Islamic Commercial Bank Financing in Indonesia Period 2014 to 2019 - Shihabudin Shihabudin; Sanjoyo Sanjoyo; Yayan Hendayana (Universitas Muhammadiyah Sidoarjo, 2021)
This research background was the decline of financing distribution ratio of Sharia Commercial Banks in Indonesia as seen from the data of the Financing to Deposit Ratio (FDR) during the period of 2014 to 2019. In 2014, the Sharia Commercial Banks FDR was recorded at 86.66%, it went down to 79.10% in 2019, meanwhile according to Bank Indonesia’s regulation in 2019, the intermediation ratio for all banks should be in the range of 84 to 94%. Compared to Sharia Business Unit and Conventional Commercial Banks, Sharia Commercial Banks, during the research period, had a lower FDR. The low FDR of Sharia Commercial Bank showed that the role of intermediation was sub-optimal and that there was considerable room for finance expansion. Suspected factors affecting the distribution of financing of Sharia Commercial Banks in this researchwere limited to Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Bonus of Bank Indonesia Certificates Syariah (SBIS), and Inflation. The results showed that the CAR, NPF, SBIS, and Inflation variables altogether had a significant effect on Sharia Commercial Bank Financing. While partially, only NPF variable had a significant effect on Sharia Commercial Bank Financing, with a regression coefficient of -2458,047, meaning that each 1% increase in the NPF will reduce Sharia Commercial Bank Financing by 2,458,047 billion Rupiah. The research results implication is that one way to optimize Sharia Commercial Bank financing in Indonesia is to reduce the level of Non-Performing Financing (NPF) at those banks